2014
DOI: 10.1002/rra.2784
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sediment Hydraulic Conductivity in River Reaches and its Potential Use to Evaluate Streambed Clogging

Abstract: Streambed substrates have pervasive effects on stream biodiversity and biogeochemistry. The excessive input of fine sediments in streams and the subsequent alteration of the physical characteristics of streambed substrates are considered today as a major environmental issue. The estimation of streambed hydraulic conductivity (K) may be simpler than other estimations of reach-scale physical characteristics and could serve to quantify the alterations of streambeds across stream networks. In this study, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 59 publications
2
66
0
Order By: Relevance
“…The fine sediment content of hyporheic substrates (subsurface sediments) was found to be significantly greater at the riffle heads in this study, reflecting the widely reported characteristics of vertical hydraulic exchange (VHE). Downwelling water is typically associated with the transport of sediment into the river bed at the head of riffles, whilst upwelling water, often at the riffle tail, has the potential to flush fine sediments from interstitial spaces (Huettel et al, 1996;Ren & Packman, 2007;Datry et al, 2015). A number of other studies have also reported greater quantities of fines in the riffle head associated with downwelling water and flows during high discharge events Dole-Olivier & Marmonier, 1992;DoleOlivier et al, 1997;Saenger et al, 2005).…”
Section: Riffle-scale Variability In Benthic Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fine sediment content of hyporheic substrates (subsurface sediments) was found to be significantly greater at the riffle heads in this study, reflecting the widely reported characteristics of vertical hydraulic exchange (VHE). Downwelling water is typically associated with the transport of sediment into the river bed at the head of riffles, whilst upwelling water, often at the riffle tail, has the potential to flush fine sediments from interstitial spaces (Huettel et al, 1996;Ren & Packman, 2007;Datry et al, 2015). A number of other studies have also reported greater quantities of fines in the riffle head associated with downwelling water and flows during high discharge events Dole-Olivier & Marmonier, 1992;DoleOlivier et al, 1997;Saenger et al, 2005).…”
Section: Riffle-scale Variability In Benthic Communitiesmentioning
confidence: 99%
“…This pattern of fine sediment deposition (typically sand-and silt-sized fractions of B2 mm; Wentworth, 1922;Jones et al, 2012) directly influences the structure and composition of invertebrate communities (Brunke & Gonser, 1999) but also the nature of vertical hydrological exchange (Leek et al, 2009;Hartwig & Borchardt, 2015;Datry et al, 2015). Consequently, the dynamic pattern of vertical hydraulic exchange exerts a strong influence on physical and chemical conditions such as temperature, oxygen concentrations and the residence time of water (Olsen & Townsend, 2003;Krause et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that neither K v nor lnK v was normally distributed at the 95% confidence level, except for lnK v in January 2016 (N = 31, p = 0.000 for K v in July 2015; N = 31, p = 0.002 for lnK v in July 2015; N = 30, p = 0.000 for K v in January 2016; N = 30, p = 0.318 for lnK v in January 2016). Previous research showed that streambed hydraulic conductivity was not normally distributed across 101 reaches or that K v had a lognormal distribution [30,31]. During the two test periods, the high values of K v were observed in the center of the channel and (Figure 3a,b).…”
Section: Vertical Hydraulic Conductivitymentioning
confidence: 76%
“…Previous research showed that streambed hydraulic conductivity was not normally distributed across 101 reaches or that Kv had a lognormal distribution [30,31]. During the two test periods, the high values of Kv were observed in the center of the channel and (Figures 3a,b).…”
Section: Vertical Hydraulic Conductivitymentioning
confidence: 77%
“…The results suggested that neither Kv nor lnKv was normally distributed at the 95% confidence level, except for lnKv in January 2016 (N = 31, p = 0.000 for Kv in July 2015; N = 31, p = 0.002 for lnKv in July 2015; N = 30, p = 0.000 for Kv in January 2016; N = 30, p = 0.318 for lnKv in January 2016). Previous research showed that streambed hydraulic conductivity was not normally distributed across 101 reaches or that Kv had a lognormal distribution [30,31]. During the two test periods, the high values of Kv were observed in the center of the channel and (Figures 3a,b).…”
Section: Vertical Hydraulic Conductivitymentioning
confidence: 77%